PI3K pathway activation in severe asthma is linked to steroid insensitivity and adverse outcomes - Sekiko Uehara, BSc; Keita Hirai, PhD; Toshihiro Shirai, MD, PhD; Taisuke Akamatsu, MD, PhD; Kunihiko Itoh, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Patients with severe asthma may demonstrate reduced sensitivity to steroid treatment. However, the implications of this reduced responsiveness for clinical outcomes and the underlying mechanisms remain unclear. Objective: The aim of this study was to investigate whether steroid sensitivity in patients with asthma is related to severity and clinical outcomes and to elucidate the role of inflammatory pathways in reducing steroid sensitivity. Methods: This observational study of 169 asthma patients, with 161 followed for 1 year, involved isolation of peripheral blood mononuclear cells. These cells were treated with dexamethasone, and the mRNA expression of FKBP5, which is a marker of steroid sensitivity, was measured. To explore the mechanism underlying the reduced steroid sensitivity, cells were exposed to PI3K and MAPK inhibitors in combination with dexamethasone. Results: A total of 53 patients diagnosed with severe asthma exhibited markedly diminished sensitivity to steroids compared with those with nonsevere asthma. Reduced steroid sensitivity has emerged as a critical risk factor for failure to experience clinical remission and exacerbation. This relationship between reduced steroid sensitivity and disease severity and adverse outcomes was confirmed at the 1-year follow-up. Mechanistic investigations revealed that the degree of recovery from steroid sensitivity after PI3Kδ/γ inhibitor treatment was significantly greater in patients with severe asthma than in those with nonsevere asthma, a finding confirmed at the 1-year follow-up. Conclusions: Patients with severe asthma demonstrate reduced steroid sensitivity, which results in unfavorable clinical outcomes. Conversely, inhibition of the PI3K pathway significantly improves steroid sensitivity.